#TITLE_ALTERNATIVE# - HISYAM WISANANDA (NIM : 10109006); Pembimbing : Dr. Sapto Wahyu Indratno, MASYHAR
In this final project, we study the parameter estimation of the solution of dynamical system equations based on the Maximum Likelihood Estimation and Ordinary Least Squares methods. Some limited discrete data are used in the estimation. Especially in this report, the logistic equation system is used to study the influences of the amount and the deployment of field data on the required parameters in the logistic equation system. Experimental results show that the amount and the deployment of field data signifcantly affect on the result of parameters estimation .....